NATURAL POLYMER GRAFTED WITH SYNTETHIC MONOMER BY MICROWAVE FOR WATER TREATMENT - A REVIEW - Muñoz Prieto, Efrén de Jesús; Rivas, Bernabé; Sánchez, Julio (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractIn this study, the use of natural polymers grafted with synthetic monomers to obtain copolymers for specific applications is revised. This review highlights current uses of microwave heating, in the grafting modifications of naturalpolymers, with other synthetic monomers and explores methodology of this technique. Microwave assisted and microwave initiated synthesized graft copolymers show superior flocculation characteristics when compared with graft copolymers produced by conventional methods. Synthesis,mechanism and characterization of these materials by different analytical techniques such as spectroscopic analysis and others are reviewed. We explore information concerning the development and characterization of grafting polymers, which have been receiving enlarged attention in recentyears as flocculants for water treatment. The effectiveness of flocculation for applications in reduction of pollutants in wastewater is also evaluated. Keywords: Copolymer, Flocculant, Grafting, Microwave, Wastewater